Dostępność transportowa Szadku - Wiśniewski, Szymon (Biuletyn Szadkowski, 2014)
This article describes transport accessibility of Szadek - a small town in Łódź voivodeship. To this end, three major aspects were analysed: potential accessibility, functioning of public transport and effectiveness of individual transport. The findings were placed in the context of accessibility analyses for the remaining 43 towns of Łódź voivodeship, which enabled identification of the degree of Szadek's accessibility in the settlement network of the region.